Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 102438 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Limosa limosa (Linnaeus, 1758)" ] } The dataset includes 102438 records from 265 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0004776-160118175350007/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences